(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Lip moisturizer is a wax-like substance that is applied topically to the lips to moisturize and relieve chapped or dry lips, angular cheilitis, stomatitis, or cold sores. The primary purpose of a lip moisturizer is to provide an occlusive layer on the lip surface to seal moisture in lips and protect them from external exposure. Dry air, cold temperatures, and wind all have a drying effect on skin by drawing moisture away from the body. This study utilized quantitative research methods in the study. Purposive sampling was composed of five STEM students and five science experts. The instrument used in this study was a questionnaire. Part 1 of the questionnaire included the profile of the respondents. Part 2 of the questionnaire consists of criteria in assessing the acceptability of Santan flower as a lip moisturizer. Part 3 of the questionnaire consisted of suggestions formulated by the respondents to test the acceptability of the lip moisturizer. The questionnaire was distributed to respondents. Researchers used lip moisturizers to mainly protect our lips. A lip moisturizer can protect and relieve lip dryness. After conducting several trial-and-errors, the researchers conducted an extensive reading to improve the organic lip moisturizer. The researchers used Santan flower. The researcher conducted a test to determine the effectiveness and safety of Santan flower as a lip moisturizer.